DEVELOPMENT AND OPTIMIZATION OF A FAST-DISINTEGRATING ORAL FILM OF MONTELUKAST SODIUM FOR PEDIATRIC USE (Journal of Medical & Health Sciences Review, 2025)
Montelukast sodium is a widely prescribed leukotriene receptor antagonist for pediatric asthma and allergies. Conventional formulations face challenges in administration for children. This study aimed to develop and optimize a patient-centric, fast-dissolving oral film (FDOF) of Montelukast sodium using a natural superdisintegrant, Musa paradisiaca (plantain) powder, specifically for pediatric use. A 3² full factorial design was employed. The concentrations of film-forming polymer (HPMC E15 LV, X₁: 250, 500, 750 mg) and superdisintegrant (Musa paradisiaca powder, X₂: 50, 100, 200 mg) were selected as independent variables. Disintegration time (Y₁) and percent druga release at 5 minutes (Y₂) were the dependent variables. Ninea formulations (F1-F9) were prepared by solvent casting and evaluated for thickness, weight variation, folding endurance, surface pH, drug content, in vitro drug release, and mechanical properties. The optimized batch underwent stability studies for 3 months as per ICH guidelines. The optimized formulation (F7), containing 250 mg HPMC and 200 mg Musa paradisiaca powder, demonstrated excellent properties: a rapid disintegration time of 18.2 ± 1.1 seconds, drug release of 99.1 ± 0.8% in 5 minutes, drug content of 99.4 ± 0.9%, and a patient-friendly surface pH of 6.72. Mechanical characterization revealed a tensile strength of2.28 MPa and percent elongation of 3.2%, indicating good handling strength and flexibility. Stability studies confirmed the robustness of the formulation. The successfully developed FDOF of Montelukast sodium, optimized using a systematic QbD approach, presents a promising, palatable, and effective alternative to conventional pediatric dosage forms, potentially enhancing compliance and therapeutic outcomes in the target population.